Sufism and the Contention of Value in the Public Space - Abdul Kadir Riyadi; Ika Yunia Fauzia; Khoirul Umami; Andi Suwarko (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
Contention of discourse does dominate the feature of our modern public space. But contention of value, while it is subtle and may not be discernable, is more essential. What appears at the surface is actually the result of what happens within. This paper discusses the problem of value contention in the public space, particularly by giving attention to the way that Sufism’s value may be involved in it. It brings forward multiple premises. On the one hand, it argues against the Western proposition that public space, especially in its rational and critical form, can only emerge in the Western setting. On the other, it problematizes the so-called Islamic public space that, while it is rational and critical, becomes a battlefield like a sphere to which religious values fall victim. In this whole situation -the paper argues- Sufi strategy to stay away from public space while at the same time making an internal consolidation to preserve its ontological security, is the proper way. Sufism itself became a victim of the free public space when it is involved directly in it, especially where secularism and liberalism prevail. Various new forms of Sufism, such as neo-sufism, hybrid-sufism, urban-sufism, and the like, are not expression of its ability to adapt to new situation but a manifestation of its failure to preserve its essence.